KEEFEKTIFAN MODEL PEMBELAJARAN GUIDE READING DENGAN TEKNIK DIRECTED READING THINKING ACTIVITIES DI SEKOLAH DASAR - Alif Mudiono (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: Effectiveness of a guide reading teaching model with the directed reading thinking activities technique in elementary schools. The purpose of the research was to describe an effectiveness of a guide reading teaching model with the directed reading thinking activities technique (DRTA) in elementary schools which was tried in extended scale in Blitar city and regent.The data were a description of effectiveness of a sylaby and effectiveness of teaching implementation. The subjects were Indonesia language teachers in four grade elementary schools. The collected data were analysed by the following procedures: (1) check the data validity, (2) data identification and classification, and (3) data analysis conducted by counting procentage, and also determining results and discussion.The mean of effectiveness of an effectiveness of a guide reading teaching model with the directed reading thinking activities technique (DRTA) was 40 (90,90%) elementary schools categorised very effective.  It means teaching Indonesia Language can be imprved by implemention of an effectiveness of a guide reading teaching model with the directed reading thinking activities technique (DRTA).Abstrak: Penelitian ini bertujuan mendeskripsikan keefektifan model pembelajaran guided reading dengan teknik Directed Reading Thinking Activities (DRTA) di SD yang diujicobakan dalam skala luas di Wilayah Kota dan Kabupaten Blitar. Data berupa deskripsi keefektifan silabus/RPP dan keefektifan pelaksanaan pembelajaran. Subjek penelitian  adalah guru bahasa Indonesia di kelas IV SD. Data dianalisis dengan rancangan deskriptif melalui prosedur: (1) pengecekan keabsahan data, (2) mengidetifikasikan dan pengklasifikasian data, dan (3) analisis data dilakukan dengan menghitung persentase, serta menentukan hasil dan pembahasannya. Berdasarkan analisis data diperoleh temuan penelitian keefektifan RPP/Silabus nilai rata-rata 60,50 (89,23%) kategori sangat efektif. Keefektifan pembelajaran model guided reading dengan teknik DRTA diperoleh nilai rata-rata 40 (90,90%) kategori sangat efektif. Dengan demikian, pembelajaran Bahasa Indonesia di SD dapat ditingkatkan melalui penerapan model guided reading dengan teknik DRTA.